On Value Distribution of Differential Polynomials of Meromorphic Functions - Banerjee, Dibyendu; Ghosh, Ishita (Journal of Nepal Mathematical Society, 2026)
In a recent paper, Fan et. al. showed that for a non-homogeneous differential polynomial formed with a non-constant meromorphic function f,  Θ(a, φ(f)) is bounded above by 1. In this paper, we extend two results for differential polynomials formed with two meromorphic functions.